Adaptabilitas struktur pada rumah panggung kayu di Kabupaten Bima dalam konteks budaya seismik lokal - Agus Dwi Hariyanto; Sugeng Triyadi; Andry Widyowijatnoko (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Earthquake-prone environmental conditions require the vernacular community in Bima Regency to adapt by carrying out 'innovations' in their stilt houses' structural and construction systems. The bottom structure tends to remain, while the top tends to change. This study aimed to identify the differences in the types of wood joints between the elements and the roof construction on wooden stilts of Mbawa, Maria, Sambori, and Kole Village, Bima Regency, in the context of their adaptability to earthquakes. Case studies through observation and documentation are carried out for data collection and identification processes. The documentation results are then analyzed to ensure the connection type between the elements on each part of the roof truss. Five types of roof truss construction are found, each with some wood connection type: pin, rigid, and friction joint. The integration between joints of the roof truss with the unique construction developed to date has proven to adapt to earthquake-prone environments. The changes made by the community to improve the seismic adaptability of uma panggu show that the local seismic culture is still developing in Bima Regency.